Outcome of immune checkpoint inhibitors in patients with extensive-stage small-cell lung cancer and brain metastases - Wang, Chunyu; Mu, Shuai; Yang, Xuhui; Li, Lingling; Tao, Haitao; Zhang, Fan; Li, Ruixin; Hu, Yi; Wang, Lijie (Frontiers in Oncology, 2023)
Abstract Objectives: Brain metastases (BMs) are common in extensive-stage small-cell lung cancer (SCLC) and are underrepresented in pivotal clinical trials that demonstrate the efficacy of immune checkpoint inhibitors (ICIs). We conducted a retrospective analysis to assess the role of ICIs in BM lesions in less selected patients. Materials and Methods: Patients with histologically confirmed extensive-stage SCLC who were treated with ICIs were included in this study. Objective response rates (ORRs) were compared between the with-BM and without-BM groups. Kaplan‒Meier analysis and the log-rank test were used to evaluate and compare progression-free survival (PFS). The intracranial progression rate was estimated using the Fine-Gray competing risks model. Results: A total of 133 patients were included, 45 of whom started ICI treatment with BMs. In the whole cohort, the overall ORR was not significantly different for patients with and without BMs (p = 0.856). The median progression-free survival for patients with and without BMs was 6.43 months (95% CI: 4.70-8.17) and 4.37 months (95% CI: 3.71-5.04), respectively (p =0.054). In multivariate analysis, BM status was not associated with poorer PFS (p = 0.101). Our data showed that different failure patterns occurred between groups, with 7 patients (8.0%) without BM and 7 patients (15.6%) with BM having intracranial-only failure as the first site progression. The cumulative incidences of brain metastases at 6 and 12 months were 15.0% and 32.9% in the without-BM group and 46.2% and 59.0% in the BM group, respectively (Gray’s p<0.0001). Conclusions: Although patients with BMs had a higher intracranial progression rate than patients without BMs, the presence of BMs was not significantly associated with a poorer ORR and PFS with ICI treatment in multivariate analysis.